“PANAWA” Animation Movement Design: Rat Character With Human Personality - Eva Aulia; Christian Aditya (Universitas Multimedia Nusantara, 2017)
Good animation movie needs to be communicative and deliver its meaning to the audience. One of the most important aspects is to design an effective movement for the animation. In movement, the thoughts and characteristics of a character are shown. Expression of a characters can be seen through their movement and body gestures. Body gestures show us an expression, emotions, traits, thoughts, and each different characters. Characters don’t move effectively if the movement doesn’t correspond to its characteristics. To understand the characteristics we need to understand each characters physiology, sociology, and psychology. In this research, the author explains and analyze the process of designing a rat movement with a human personality. Keywords: animation, movement, body language, expression